Acculturation, vitality, and bilingual healthcare - Bourhis, Richard Y.; Montreuil, Annie (The Oxford handbook of acculturation and health, 2017)

Talk COVID to me: Language rights and canadian government responses to the pandemic - Chouinard, Stéphanie; Normand, Martin (Canadian Journal of Political Science, 2020)
Since the COVID-19 outbreak, a gradual loosening of linguistic obligations in public institutions and governments has been observed in various jurisdictions in Canada. This article argues that in addition to legal requirements to provide minority language services, it is not justifiable for governments to suspend or curtail such services in an emergency situation, for reasons pertaining to public safety and public health. After performing a survey and analysis of government actions against their constitutional, legislative, and policy language obligations to highlight best practices and deficiencies, we discuss the policy implications of these actions. In conclusion, the article considers how governments could better uphold their language obligations in times of emergency.

Situation des populations de langue anglaise au Québec et de langue française au Canada hors Québec : résultats de l’Enquête sur la population de langue officielle en situation minoritaire de 2022 - Pépin‑Filion, Dominique; Cornelissen, Louis; Lemyre, Étienne (Statistique Canada, 2024)
Le présent rapport et l’Enquête sur la population de langue officielle en situation minoritaire de 2022 ont bénéficié du soutien financier et de la collaboration soutenue du ministère du Patrimoine canadien. Cette étude a pu être réalisée grâce au travail de longue haleine de plusieurs équipes et personnes qui se sont relayées au fil des ans pour planifier, concevoir, préparer, tester, réaliser, assurer la qualité des données, documenter, analyser et diffuser cette enquête d’envergure. Les auteurs tiennent à remercier toutes les personnes qui ont participé à ce processus, en particulier, Marie Desnoyers, Éric Caron Malenfant, Daniel Pereira, Claude Girard, Marie‑ Hélène Toupin, Danielle Léger et Catherine Dufour. Plusieurs autres membres du personnel actuel ou passé de Statistique Canada ont contribué de manière importante à cette enquête au fil du temps, dont Siramane Coulibaly, Catherine Frigon, Julien Acaffou, Paul Brisson, Sara Tello, Jean‑Pierre Corbeil, Émilie Lavoie, Deniz Do, Jean‑François Nault, Guylaine Dubreuil, Isabelle Lévesque, Daphné Allard Gervais, Geneviève Caron, Geanina Popescu et Dominique Pérusse, de même que les équipes internes des activités de collecte et de traitement des données. Pour leur soutien, leurs conseils et leur aide à la production du rapport, merci à Laurent Martel, Daphne Fernandes, Juliane Oliveira Pisani Martini et Pierre‑France Bondesen‑David. Soulignons également l’expertise et l’orientation fournies par les réviseurs ainsi que les membres du comité de direction et les membres du comité scientifique de l’enquête.

Situation of English-speaking populations in Quebec and French-speaking populations in Canada outside Quebec: Results of the 2022 Survey on the Official Language Minority Population - Pépin‑Filion, Dominique; Cornelissen, Louis; Lemyre, Étienne (Statistique Canada, 2024)
This report and the 2022 Survey on the Official Language Minority Population received funding and ongoing support from the Department of Canadian Heritage. This study was made possible thanks to the tireless efforts of many different teams and individuals who, over the years, contributed to planning, designing, preparing, testing, conducting, ensuring data quality, documenting, analyzing and publishing this major survey. The authors would like to thank each and every one of them, especially, Marie Desnoyers, Éric Caron Malenfant, Daniel Pereira, Claude Girard, Marie‑Hélène Toupin, Danielle Léger and Catherine Dufour. Many other current or former Statistics Canada staff members have made, over the years, important contributions to this survey including Siramane Coulibaly, Catherine Frigon, Julien Acaffou, Paul Brisson, Sara Tello, Jean Pierre Corbeil, Émilie Lavoie, Deniz Do, Jean‑François Nault, Guylaine Dubreuil, Isabelle Lévesque, Daphné Allard Gervais, Geneviève Caron, Geanina Popescu and Dominique Pérusse, as well as the in‑house data collection and processing teams. For their support, advice and help in producing the report, thanks to Laurent Martel, Daphne Fernandes, Juliane Oliveira Pisani Martini and Pierre‑France Bondesen‑David. We would also like to acknowledge the expertise and guidance of the editors, as well as the members of the Interdepartmental Steering Committee and the survey Scientific Committee.